Gender-specific prevalence and associated factors of hypertension among elderly Bangladeshi people: Findings from a nationally representative cross-sectional survey - Hanif, Abu Abdullah Mohammad; Shamim, Abu Ahmed; Hossain, Md Mokbul; Hasan, Mehedi; Khan, Md Showkat Ali; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S M Mustafizur; Mitra, Dipak K; Mridha, Malay Kanti (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2020-038326 The Journal's website is at: http://dx.doi.org/10.1136/bmjopen-2020-038326